Effectiveness of afatinib after long-term gefitinib treatment for EGFR L858R and S768I compound mutation-positive lung adenocarcinoma: A case report - Ayuka Dai-Shinozaki; Jun Sakakibara-Konishi; Kanako C. Hatanaka; Kento Wakabayashi; Naofumi Shinagawa; Yoshihiro Matsuno; Yutaka Hatanaka; Satoshi Konno (Respiratory Medicine Case Reports, 2025)
Afatinib, a second-generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI), irreversibly inhibits the pan-human epidermal growth factor receptor (HER) family. It is effective in patients with lung cancer with various EGFR mutations; however, its efficacy in overcoming resistance following first-line EGFR-TKI treatment remains unclear. Here, we report the case of a 68-year-old woman with lung adenocarcinoma (pStage IA, pT1bN0M0) who underwent surgical resection in March 2012 following several previous lung cancer resections. In November 2012, postoperative recurrence with pleural dissemination led to the detection of the EGFR L858R mutation in the malignant pleural effusion specimen using peptide nucleic acid-locked nucleic acid polymerase chain reaction clamping (PNA-LNA PCR clamp). The patient was treated with gefitinib for 8 years, after disease progression with multiple lung metastases. The metastatic lesions harbored compound EGFR S768I and EGFR L858R mutations, as identified using the Oncomine Dx Target Test Multi-CDx System (ODxTT). Treatment with afatinib resulted in rapid metastatic lesion regression. Reanalysis of the previously resected surgical specimens confirmed the presence of the EGFR S768I and L858R compound mutations in all samples, which suggests that S768I was not an acquired resistance mutation. Furthermore, immunohistochemical analysis revealed an increase in HER2 and HER3 protein expression in the gefitinib-resistant specimens. These findings suggest that HER2 and HER3 upregulation may contribute to gefitinib resistance, and that afatinib may effectively target these resistance mechanisms.